2015
DOI: 10.1007/s11144-014-0825-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydroconversion of acetic acid over indium- and phosphorus-modified nickel/laponite catalysts

Abstract: Modified catalysts were prepared from laponite (LT)-supported Ni catalyst. The catalysts were characterized by specific surface area (SSA), pore size distribution (PSD), in situ X-ray diffractometry (XRD) and activity in the hydroconversion of acetic acid (AA) at 21 bar total pressure, WHSV AA =0.5-3.0 h -1 , and 260-380 °C reaction temperature. The modification generated LT-supported Ni 2 In or Ni 2 P active phases. The Ni 2 P catalyst showed hydrodecarbonylation (HDC) activity. The Ni 2 In/LT catalyst has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Harnos, Onyestyák and co‐workers investigated combination of supported Ni and In 2 O 3 in gas‐phase hydrogenation of carboxylic acids such as octanoic acid, acetic acid and decanoic acid to the corresponding alcohols (Table , entries 1–7), and they found that modification of Ni metal with In 2 O 3 improved selectivity and activity. Also, the performance was superior to the Adkins catalyst, a standard catalyst of Cu−Cr type catalyst for hydrogenation of carboxylic acid and esters.…”
Section: Heterogeneous Catalysts With Bimetallic Speciesmentioning
confidence: 99%
“…Harnos, Onyestyák and co‐workers investigated combination of supported Ni and In 2 O 3 in gas‐phase hydrogenation of carboxylic acids such as octanoic acid, acetic acid and decanoic acid to the corresponding alcohols (Table , entries 1–7), and they found that modification of Ni metal with In 2 O 3 improved selectivity and activity. Also, the performance was superior to the Adkins catalyst, a standard catalyst of Cu−Cr type catalyst for hydrogenation of carboxylic acid and esters.…”
Section: Heterogeneous Catalysts With Bimetallic Speciesmentioning
confidence: 99%